The Copyright and Authorship for Non-Biological Intelligence Self-Creation in Algerian Legislation - Tidjani, Bouzidi Ahmed (Dirasat: Shari'a and Law Sciences, 2025)
Objectives: Logarithms have enabled artificial intelligence to enter fields once exclusive to humans, allowing it to compete in creativity. AI now produces original works that raise questions among intellectual property scholars regarding whether to grant authorship to AI or exclude it, given the implications for law and practice. This article examines the foundations for considering AI as an author in one section, and in another, discusses the reasons for exclusion. A third section proposes a specific system for AI-generated works. Methods: The article employs a comprehensive, descriptive, and comparative approach to address the issue, analyzing AI creations in light of authorship criteria and exploring significant legal and judicial trends adapting AI's originality within the authorship framework. Results: The article concludes that national and international laws restrict authorship to human individuals, granting them rights as extensions of their personality while denying this status to AI. Legal scholars remain divided: some view AI creations as authorship, while others argue that such status should be exclusive to humans. Conclusions: The article suggests classifying AI works as databases, as they derive from original, protected works. It also proposes applying the right of attribution to AI-generated works, sharing benefits among the programmer, AI owner, or those who contributed creatively, and the public domain, based on principles of justice and logic.